The Influence of Creativity, Transformational Leadership, Job Engagement, and Job Satisfaction on employee performance - Fajar Rezeki Ananda Lubis (Cita konsultindo, 2023)
Errors in bureaucratic management are often detrimental to many companies. Management and worker quality are determinants of the company's progress, as happened in the PTPN III and IV plantation companies, which had decreased income in recent years. This study uses an explanatory research type to explain the causal relationship between several variables. So the need for research to determine the determinants of employee performance at PT. Nusantara Plantations III and IV in North Sumatra. The results showed that Transformational Leadership, Job Engagement, and Job Satisfaction significantly influence employee performance. Thus, if the aspects contained in the organizational culture can be implemented correctly, it can dramatically improve the performance of implementing employees at PTPN III and IV. Meanwhile, employee creativity does not have a significant influence on employee performance. Thus it can be concluded that the aspects displayed by research respondents through answers to each statement related to employee creativity are not yet at an optimal level, so the level of significance is also not optimal in influencing the performance of PTPN III and IV implementing employees.